Hallyu dan Pengaruhnya pada Perkembangan Objek Wisata Tematik Korea Selatan - Yuni Wachid Asrori; Supriadianto Supriadianto (Sekolah Vokasi, Universitas Gadjah Mada, 2019)
Korean Pop phenomenon, Hallyu, affect to the development of various tourism objects in Seoul and South Korea in general. Hallyu as a new wave is popular among young generations, not only as an entertainment, but also as tourist attraction in South Korea. This phenomenon increased number of travelers to South Korea year by year. This descriptive research analyze qualitatively several tourism objects well known as shooting site of several popular Korean dramas where travelers may experience several things related to Korean dramas. There are not only K-Pop experiences that make Korean tourism popularity increasing rapidly, but also the government rules have also been paving the important way to promote and develop Korean tourism destinations